Relation Between Body Composition, Systemic Inflammatory Response, and Clinical Outcomes in Patients Admitted to an Urban Teaching Hospital with COVID-19. Issue 8 (3rd June 2021) - McGovern, Josh; Dolan, Ross; Richards, Conor; Laird, Barry J; McMillan, Donald C; Maguire, Donogh
ABSTRACT: Background: COVID-19 has been associated with cases of severe respiratory illness, admissions to intensive therapy units (ITUs), and high mortality rates. Objectives: The aim of the present study was to examine the relation between computed tomography- body composition (CT-BC) measurements, systemic inflammation, and clinical outcomes in those with COVID-19. Methods: Patients who presented to our institution between March 17 and May 1, 2020, with a positive PCR test for COVID-19 or characteristic radiological changes, were assessed for inclusion. Data collected included general demographic details, clinicopathological variables, poGPS, NLR, CT-BC measurements, and clinical outcomes including ITU admission and 30-d mortality, of those admitted. Results: Sixty-three patients met the study inclusion criteria. Forty-two patients (67%) were aged ≥70 y, 30 (47.6%) were male and 34.9% ( n = 22) had a poGPS ≥1. ITU admission was significantly associated with a high VFA ( P < 0.05). Thirty-day mortality was associated with high VFA ( P < 0.05) and low SMI ( P < 0.05). Conclusions: Sarcopenia in the presence of obesity was associated with clinical outcomes including greater 30-d mortality.